Pemanfaatan Sosial Media Instagram dalam Meningkatkan Citra Lembaga Pengembangan Insani Dompet Dhuafa - Ahmad Tajudin; Asep Gunawan; Sutisna Sutisna (Universitas Pahlawan Tuanku Tambusai, 2023)
Currently, technology is developing into an information service platform for various circles of society. The research provides important insights into how charities like Dompet Dhuafa can use Instagram social media as a powerful tool to improve their image. This study aims to find out the procedures of institutions in improving image, and find out what strategies institutions do to achieve an image. The research method used is qualitative method, where researchers conduct interviews with one of the resource persons from the human development institution of dompet dhuafa, as well as make observations, and documentation. The result of this research discussion is the strategy used by the institution in an effort to improve and maintain the image it has received through Instagram social media